Investigation of the Exchange Rate Pass-through Effect on Domestic Producer and Consumer Prices in Turkey - EMEK, Ömer Fazıl; DÜŞÜNCELİ, Faruk; DORU, Ömer (İstanbul iktisat dergisi (Online), 2021)
This study analyzes the effect of nominal exchange rate changes in the 2005:1–2020:4 period, applying econometric methods to examine Turkey’s economy at the level of consumer price index (CPI) and producer price index (PPI). For this purpose, short- and long-term co-integration relationships between Turkey’s inflation, exchange rate, industrial production, and import unit value indices in the period 2005–2020 were investigated. Two different models were created based on CPI and PPI variables as representative of the inflation rate. We used the auto-regressive distributed lag (ARDL)boundary test to determine the short and long term relationship between variables. According to ARDL boundary test results, in the CPI model, a 1% increase in the industrial production index, nominal exchange rate, and import unit value index causes 0,37%, 0,69%, and 0,58% increases in consumer prices, respectively. In the PPI model, a 1% increase in the nominal exchange rate and import unit value index causes 0,82% and 0,73% increases in producer prices, respectively. These findings indicate that exchange rate, industrial production, and import price have an impact on domestic consumer prices in Turkey. Similarly, it appears that exchange rate and import prices affect domestic producer prices, also demonstrating the existence of an exchange rate pass-through effect on both domestic producer and domestic consumer prices. The results of the study are in congruence with previous literature on the subject.